Research and Prospect of Reservoir Landslide Mechanism and Risk Evaluation - GUAN Yanli; JIA Ronggu; LI Yuhong; WENG Yanmei; LI Jiayan; FENG Rui (Renmin Zhujiang)
Reservoir landslides possess the characteristics of complex disaster mechanisms and high difficulty in risk prevention and control. Over the years, landslide disasters in mountainous reservoirs have caused multiple casualties and heavy economic losses worldwide, making it a key and difficult scientific and technological breakthrough in the prevention and control of geological disasters in reservoir areas. This paper reviews some cases of reservoir landslide disasters over the years and analyzes the factors influencing the development of reservoir landslides and their typical development characteristics. From the perspective of dynamic water pressure caused by the periodic change of reservoir water level "rising and falling" and the long-term softening of rock and soil, the mechanism of water-rock interaction during landslide development is expounded. The research hotspots of early identification, triggering mechanism, chain disaster, and risk assessment of reservoir bank landslide are discussed. Finally, the remaining challenges are discussed, and three urgent research directions are proposed: disaster mechanism and migration mode of reservoir landslide, efficient identification technology of landslide potential danger, and intelligent evaluation system of reservoir landslide risk.